Microcontroller-based High-way Tunnel Electrical Controlling System - Alhammady, Asem; Alsamawi, Motea; Aljamali, Mokarram; Alquradhi, Abdullatif; Elkustaban, Amin (University of Science and Technology, Yemen, 2014)
High-way tunnels play an important role in our life. Its used to solve a lot of problems such as reducing the crowds in the traffic and shortening the way from place to another. High-way tunnels have many forms like long tunnels, short tunnels and mountain tunnels. In Yemen, there are several high-way tunnels. These high-way tunnels have many problems such as repeated electricity cut off and collected water from the tunnels which result to stop vehicles to enter this tunnel. This paper suggests and implements a solution using Arduino Microcontroller to control all the electrical equipment of a highway tunnel to overcome all previous problems.